(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2025)
This article provides an in-depth characterization of a modern material with significant advantages: cellular concrete. The characterization is based on diverse mechanical and structural properties, aligning with experimental research conducted globally. Key parameters chosen for material characterization include compressive strength, elastic modulus, Poisson’s ratio, and density. A comparative analysis is conducted among six distinct experimental specimens prepared in various research studies to establish correlations with structural concrete. Following this, an applicative analysis of cellular concrete is conducted, followed by insights into its usage in Colombia. The results reveal that cellular concrete is a lightweight material, with its density varying between 400 kg/m^3 and 1900 kg/m^3, contingent upon the desired strength and constituent materials. The material demonstrates several benefits compared to structural concrete. However, its application must be carefully studied concerning the specific engineering challenge at hand. Despite its low density, it may not exhibit high mechanical strength; nevertheless, the material exhibits excellent resistance to penetration and densification, enhancing its overall appeal.